AUDIT SISTEM INFORMASI APLIKASI PENJUALAN TUNAI PADA PT AJ - Evy Herawati (CommIT (Communication and Information Technology) Journal, 2009)
The purpose of the study is to determine if general control and application control at PT AJ is sufficient in running the system of cash sale in an efficient and effective. Conclusion obtained are more adequate level of internal control reliability in handling the risks that may occur so that the information produced will be more rapid, accurate, and reliable to support decision making from management. Therefore, it is very important for companies to conduct an audit of internal control, management control, application control, particularly software application on a regular basis so that cash sale can be more reliable anymore.Keywords: audit, information system, cash sale, the company